Les paiements pour services environnementaux de la Fondation Natura Bolivia entre logiques réciprocitaires, redistributives et marchandes, - Bétrisey, Florence; Mager, Christophe (Revue Française de Socio-Économie, 2015)
La diffusion internationale des paiements pour services environnementaux (PSE) a été interprétée en 2010 par le gouvernement bolivien d’Evo Morales comme une réponse strictement néolibérale à la nécessité d’assurer une gestion durable des ressources naturelles. Supposée amener à terme à l’éviction de toute régulation autre que marchande – qu’elle s’applique à la nature ou aux rapports entre personnes –, la mise en place de PSE n’a pas été encouragée par les autorités nationales boliviennes. Des projets de PSE ont toutefois été lancés, dont les Acuerdos Reciprocos por el Agua (ARA), issus d’un partenariat public-privé dans le département de Santa Cruz. En analysant leur conception et leur fonctionnement au prisme du référentiel polanyien, nous montrons que, contrairement aux craintes gouvernementales, ces PSE ne font pas abstraction des logiques organisationnelles réciprocitaires et redistributives, ajustant au contexte local un objet global., ENG: The international dissemination of payments for ecosystem services (PES) has been interpreted in 2010 by the Bolivian government of Evo Morales as a strictly neo-liberal response to the need to ensure a sustainable management of natural resources. Supposed to contribute to the crowding-out of any other regulation than market – applied to the nature or the relationship between people – the implementation of PES was not encouraged by the Bolivian national authorities. However some PES projects stemming from a public-private partnership have been initiated at local level, as the Acuerdos Reciprocos por el Agua (ARA), in the department of Santa Cruz. Analysing their design and operating through the Polanyian framework, we show that, contrary to the government fears, these PES do not ignore the reciprocal and redistributive organisational logics, adjusting a global object to the local context.
Keywords: Bolivia; Bolivie; Polanyi; hybridity; hybridité; logique marchande; market logic; paiements pour services environnementaux; payments for ecosystem services; reciprocity; redistribution; réciprocité; sustainable management

Territoire, innovation et développement durable : l'émergence d'un nouveau régime conventionnel? - Buclet, Nicolas (Revue d'Économie Régionale & urbaine, 2011)
ENG TITLE: Territory, innovation and sustainable development: towards a new conventional regime? ABSTRACT: The paper examines the increasing number of diverse local development initiatives around the world aiming to break away from the predominant economic system. These initiatives, we argue, despite a somewhat visible disparity, largely rest on relatively similar principles, values and references. We argue that they are effectively laying the foundation for a new conventional regime more attuned to sustainable development goals. The paper analyses the characteristics of this regime, which refuses market dominance and favours reciprocal exchanges, as defined by Karl Polanyi. It is, nevertheless, necessary to question the potential and limitations of this conventional regime. (English)
Keywords: Territoire; conventions; development economics; développement durable; economic development; economics; environment; innovation; mathematical models; sustainable development; territory